2013
DOI: 10.5005/jp-journals-10024-1307
|View full text |Cite
|
Sign up to set email alerts
|

Degree of Conversion and Hardness of Two Different Systems of the VitrebondTM Glass Ionomer Cement Light Cured with Blue LED

Abstract: This study investigated the physicochemical properties of the new formulation of the glass ionomer cements through hardness test and degree of conversion by infrared spectroscopy (FT-IR). Forty specimens (n = 40) were made in a metallic mold (4 mm diameter x 2 mm thickness) with two resin-modified glass ionomer cements, Vitrebond TM and Vitrebond TM Plus (3M/ ESPE). Each specimen was light cured with blue LED with power density of 500 mW/cm 2 during 30 s. Immediately after light curing, 24h, 48h and 7 days the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 32 publications
0
0
1
Order By: Relevance
“…Additionally, the low viscosity of HEMA monomers may facilitate the mobility of reactive chains, which could increase the degree of monomer conversion [40]. The conversion of VB detected in the current study was higher than that reported in a previously published study (60-80%) [41]. This could be due to the effects of different light intensities from the curing unit.…”
Section: Degree Of Monomer Conversioncontrasting
confidence: 79%
“…Additionally, the low viscosity of HEMA monomers may facilitate the mobility of reactive chains, which could increase the degree of monomer conversion [40]. The conversion of VB detected in the current study was higher than that reported in a previously published study (60-80%) [41]. This could be due to the effects of different light intensities from the curing unit.…”
Section: Degree Of Monomer Conversioncontrasting
confidence: 79%